Resuscitation of a case of cardiac arrest complicated by resection of a giant mediastinal tumor: a case report and literature review - Ka Sha, Mu Jie; Huang, Ling; Xiong, Chen yi; Zhao, Chun yuan (Frontiers in Oncology, 2025)
This case report describes the successful resuscitation of a 54-year-old female who experienced cardiac arrest following resection of a giant mediastinal tumor (GMT). The patient’s hemodynamic collapse was attributed to mediastinal mass syndrome, mediastinal swing, and acute re-expansion pulmonary edema. This report highlights the challenges of perioperative management in GMTs, emphasizing the importance of multidisciplinary preoperative planning, continuous hemodynamic monitoring, and prompt intervention during complications. Early recognition of hemodynamic instability, coupled with adherence to advanced resuscitation protocols, is critical for improving survival in high-risk mediastinal tumor surgeries.